ANALYSIS OF LATERITE SOIL WITH PORTLAND CEMENT MIXED VARIATIONS AND THE EFFECT ON THE CBR UNSOAKED - Ahmad Ravi; Hurul 'Ain; Polonia, Betti Ses Eka; M. Hanif Faisal (P3M Politeknik Negeri Banjarmasin, 2021)
Ketapang and Kayong Utara Regency have road construction that often suffers damage before the planned life age caused by the behavior of expansive clay. The subgrade is a fundamental structure in building road construction because the subgrade will support traffic loads or construction loads. The strength and durability of the pavement structure road will depend on the properties and bearing capacity of the subgrade. Practically soil stabilization is a reinforcement engineering against foundation or subgrade by using mixed materials. Therefore, different soil improvement variations are needed. Based on the test result, the CBR value of Sukadana initially gets a 2.95% point. The CBR value for the 6% and 10 % mixture, respectively, gets 17.14% and 25.02%. The CBR value of Sungai Melayu Rayak originally get 4.65% point. Then, for the 6% and 10% mixture, the CBR values increased by 13.78% and 18%. The value of the bearing capacity of the highway soil construction can be know from the results of CBR testing on each variation. The CBR also can measure the strength of the soil. The addition of cement to the earth tends to increase the bearing capacity of the ground. It is because cement can function as a binder between soil particles with chemical compounds contained in cement.